Aspectos midiáticos e culturais do estilo cinematográfico: a mise en scène na obra de Paul Thomas Anderson - Rabelo, Thiago da Silva (2020)
The research has as its theme the midiatic and cultural aspects of film style in north american fictional cinema. The corpus is composed of two feature films directed by Paul Thomas Anderson, from which the intention is to understand mise en scène choices as formal resources influenced not only by what is rational in filmic experience, but also by the constant affective dynamics maintained between public and film. From the investigations of King (2005) and Biskind (2004) on independent American production of the 1990s, the main objective is to analyze how the director builds the mise en scène in his films in order to reveal emotional qualities to the audience, creating formal disruptions that put him on the fringes of his country's mainstream production. In this sense, the study will explore singularities that, according to Bordwell (2013), Oliveira Jr. (2013) and Aumont (2006), justify a possible opposition to the classical conventions, whether narrative or formal, established by Hollywood. For this, an in-depth analysis of Anderson's stylistic choices is performed based on the movies There Will Be Blood (2007) and Phantom Thread (2017), showing, based on the analysis of the obtained data, patterns and variations relevant to the comprehension of Anderson’s way of staging. Therefore, it is a qualitative approach research that will adopt as a method the neoformalist film analysis described by Thompson (1988). As a result, the research found that in both films Anderson is more interested in the psychological and emotional development of his characters, as well as in the relationship between them, than in narrative structures based on constant twists.